2019
DOI: 10.1016/j.psicod.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Eficacia de una app psicoeducativa para reducir el sexismo en adolescentes

Abstract: El presente estudio evalúa la eficacia de una intervención consistente en el uso de una aplicación móvil en formato juego dirigida a reducir el sexismo en adolescentes. Se lleva a cabo un estudio cuasiexperimental pretest-postest con grupos de intervención y de control. Participan 369 estudiantes de Educación Secundaria Obligatoria de entre 12 y 17 años de la provincia de Valencia, de los cuales 196 se asignan a la condición de intervención con la aplicación y 173 al grupo control. Se evalúa sexismo hostil y b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
0
6
0
2
Order By: Relevance
“…It contains activities to foster critical and reflective thinking by promoting the development of prosocial skills and attitudes, questioning socially accepted mistaken beliefs, and identifying negative messages. This app has been found to be effective for secondary school students in reducing distortions about romantic love and sexist attitudes (Navarro-Pérez, Carbonell, & Oliver, 2019). Braciszewski et al (2018) recently developed an intervention involving a mobile application, iHeLP, which, in a pilot study with a small sample, proved effective in reducing marijuana use in adolescents residing in care facilities.…”
Section: Ict-based Intervention Tools In Residential Care Centersmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains activities to foster critical and reflective thinking by promoting the development of prosocial skills and attitudes, questioning socially accepted mistaken beliefs, and identifying negative messages. This app has been found to be effective for secondary school students in reducing distortions about romantic love and sexist attitudes (Navarro-Pérez, Carbonell, & Oliver, 2019). Braciszewski et al (2018) recently developed an intervention involving a mobile application, iHeLP, which, in a pilot study with a small sample, proved effective in reducing marijuana use in adolescents residing in care facilities.…”
Section: Ict-based Intervention Tools In Residential Care Centersmentioning
confidence: 99%
“…The Liad@s app is available and free to download for android and iOS. The entire contents and domains, the different tests and the scoring system used to develop targeted skills is fully described in Navarro-Pérez et al (2019). In addition to attending the explanatory talk with instructions for using the app, the inclusion criterion for participants to remain in the intervention group was to individually obtain a minimum of 2,500 points in the game, as proof of commitment and evidence that they played with the app enough to become familiar with its contents and procedures.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…Various intervention programs have proved to be effective at reducing sexism levels in Spanish adolescents (Carrascosa, Cava, Buelga, & de Jesus, 2019;Navarro-Pérez, Carbonell, & Oliver, 2019). Most of these programs have several characteristics in common: a) they had at least 11 hours of training b) they were taught by specialized professionals, c) they used gamification and role-play and, d) sexism was related to romantic myths.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Studies have identified the virtual sphere as a new space conveying many violent situations both in the peer group [8] and in dating relationships [9]. Thus, adolescents' usage of ICT through online applications, video games, etc., should be considered useful to prevent violence and, specifically, partner violence [10]. Following the review carried out by Navarro-Pérez et al [11] on ICT-based intervention tools, the following stand out for the prevention and intervention of Teen Dating Violence (TDV): Teen Choices program [12]; DetectAmor [13] and other mobile applications with a high level of effectiveness such as the Liad@s app [11,14], of an entertaining and educational nature, which aims to help adolescents to have egalitarian and non-toxic couple relationships, and involves having less sexist attitudes, identifying myths about love, and reducing situations of violence in their relationships.…”
Section: Introductionmentioning
confidence: 99%